Perineural capsaicin induces the uptake and transganglionic transport of choleratoxin b subunit by nociceptive c-fiber primary afferent neurons. (17th December 2015) - Oszlács, O.; Jancsó, G.; Kis, G.; Dux, M.; Sántha, P.
Graphical abstract: Highlights: TRPV1 agonists induce labeling of C-fiber afferents with choleratoxin B subunit. Injured C-fiber primary sensory neurons change their ganglioside phenotype. Chemically injured C-fiber primary afferent neurons transport choleratoxin B subunit. Electron microscopy reveals choleratoxin B subunit in unmyelinated dorsal root axons. Perturbation of GM1 ganglioside metabolism may modulate nociceptor function. Abstract: The distribution of spinal primary afferent terminals labeled transganglionically with the choleratoxin B subunit (CTB) or its conjugates changes profoundly after perineural treatment with capsaicin. Injection of CTB conjugated with horseradish peroxidase (HRP) into an intact nerve labels somatotopically related areas in the ipsilateral dorsal horn with the exceptions of the marginal zone and the substantia gelatinosa, whereas injection of this tracer into a capsaicin-pretreated nerve also results in massive labeling of these most superficial layers of the dorsal horn. The present study was initiated to clarify the role of C-fiber primary afferent neurons in this phenomenon. In L5 dorsal root ganglia, analysis of the size frequency distribution of neurons labeled after injection of CTB-HRP into the ipsilateral sciatic nerve treated previously with capsaicin or resiniferatoxin revealed a significant increase in the proportion of small neurons. In the spinal dorsal horn, capsaicin or resiniferatoxin pretreatment resulted in intense CTB-HRP labeling of the marginal zone and the substantia gelatinosa. Electron microscopic histochemistry disclosed a dramatic, ∼10-fold increase in the proportion of CTB-HRP-labeled unmyelinated dorsal root axons following perineural capsaicin or resiniferatoxin. The present results indicate that CTB-HRP labeling of C-fiber dorsal root ganglion neurons and their central terminals after perineural treatment with vanilloid compounds may be explained by their phenotypic switch rather than a sprouting response of thick myelinated spinal afferents which, in an intact nerve, can be labeled selectively with CTB-HRP. The findings also suggest a role for GM1 ganglioside in the modulation of nociceptor function and pain.